Nine complete chloroplast genomes of the Camellia genus provide insights into evolutionary relationships and species differentiation - Yanfei Cai; Min Tian; Yingjie Yang; Ziming Shi; Peifei Zhao; Jihua Wang (Scientific Reports)
Abstract The genus Camellia, known for species such as Camellia japonica, is of significant agricultural and ecological importance. However, the genetic diversity and evolutionary relationships among Camellia species remain insufficiently explored. In this study, we successfully sequenced and assembled the complete chloroplast (cp) genomes of nine Camellia accessions, including the species Camellia petelotii, and eight varieties of C. Japonica (C. Japonica ‘Massee Lane’, C. Japonica ‘L.T.Dees’, C. Japonica ‘Songzi’, C. Japonica ‘Kagirohi’, C. Japonica ‘Sanyuecha’, C. Japonica ‘Xiameng Hualin’, C. Japonica ‘Xiameng Wenqing’, and C. Japonica ‘Xiameng Xiaoxuan’). These genomes exhibited conserved lengths (~ 156,580–157,002 bp), indicating minimal variation in genome size. They consistently predicted 87 protein-coding genes, although variations were observed in the rRNA and tRNA genes. Structural and evolutionary analyses revealed the highly conserved nature of these cp genomes, with no significant inversions or gene rearrangements detected. Consistent codon usage patterns were observed across these accessions. Five hypervariable regions (rpsbK, psbM, ndhJ, ndhF, and ndhD) were identified as potential molecular markers for species differentiation. Phylogenetic analysis of 82 accessions from the Camellia genus, along with outgroup accessions revealed close genetic relationships among certain C. japonica varieties, including Songzi, Sanyuecha, L.T.Dees, and Kagirohi, which formed sister groups. Massee Lane was located within Sect. Camellia. Moreover, Xiameng Hualin, Xiameng Wenqing, Xiameng Xiaoxuan, and C. petelotii demonstrated a strong genetic affinity. These findings provide valuable insights into the structural and evolutionary dynamics of Camellia cp genomes, contributing to species identification and conservation.